Sowing operation direction and population densities in corn growing - Correa, Rafael D. G. [UNESP]; Furlani, Carlos E. A. [UNESP]; Zerbato, Cristiano [UNESP]; Oliveira, Danilo T. de [UNESP]; Noronha, Rafael H. de F.; Warikoda, Newton K. [UNESP] (Univ Federal Campina Grande, 2019)
Among the factors that may influence corn yield are sowing operation direction and plant population, since they alter the shade index between crop rows, and consequently the efficiency of interception of the photosynthetically active radiation by the leaves of plants. The aim of this study was to evaluate the influence of sowing direction and plant populations on P2830VYH hybrid corn yield. The experiment was conducted at the facilities of FCAV-UNESP, latitude 21 degrees 14' S and longitude 48 degrees 16' W in Jaboticabal (SP). The treatments were composed of three sowing directions (North-South, Northeast-Southwest, and East-West) and three population densities (40,000, 60,000 and 80,000 plants ha(-1)). The treatment with 80,000 plants ha(-1) had the lowest cost per sack of corn and profitability 21% higher than that of the treatment with 60,000 plants ha(-1), and 45% higher than that of the treatment with 40,000 plants ha(-1). Sowing direction had no influence on grain yield when environmental conditions were favorable to the development of the crop. Lower plant densities lead to higher individual results in relation to the number of cobs, length of cobs and number of grains per row.
Keywords: Zea mays L.; sowing configuration; plant population; grain yield